Electrochemical biosensors combining aptamers and enzymatic activity: Challenges and analytical opportunities. (10th September 2021) - Rhouati, Amina; Marty, Jean-Louis; Vasilescu, Alina
Abstract: The combination between the specific recognition abilities of aptamers and the catalytic power of enzymes represents a powerful tool in bioanalysis to achieve the highly selective and sensitive detection of various molecules. Enzymes attached to biomolecules and nanomaterials facilitate the highly amplified detection of electroactive compounds. Meanwhile DNAzymes, small DNA strands showing enzyme-like activity are increasingly used as replacements of natural enzymes in electrochemical aptasensors. Moreover, nucleic acid catalysts have been integrated together with aptamer domains in aptazymes, where the aptamer-ligand interaction acts as a switch for the enzyme-like activity. The review discusses enzyme and DNAzyme based amplification, as the preferred approaches in electrochemical aptasensors. DNA and nanomaterial based signal enhancement is briefly mentioned, while a larger discussion is dedicated to aptasensors for the measurement of enzymatic activity and for the development of "universal" detection tools based on the aptamer-enzyme combination. This includes assays combining aptamers with glucometers for the detection of various molecules and promising "aptameric enzyme subunits"-yet to be integrated with electrochemical detection. The outlooks of the electrochemical biosensors coupling aptamers and enzymes are presented.